Risk, Return and Degree of Owner Involvement in Privately Held Firms - Edward Vos; Bronwyn M. Smith (The Journal of Entrepreneurial Finance and Business Ventures, 2003)
Financial theory states that the variability of an asset's return should be explained by the relative riskiness of that asset (Sharpe, 1964). This concept has been built around, and applied to, publicly-listed companies for which market information (which forms the basis of the risk and return measures) is easily visible and obtainable. Unfortunately, the fact that such information is rarely (if ever) available for small businesses, severely limits the usefulness of such a theory for privately-held enterprises. Therefore by using data from 100 small businesses and three measures of risk, this study provides empirical evidence that for small businesses, there is no significant relationship between financial returns and risk, but there is a relationship between the level of control exerted by the owners of a firm and the financial returns of that firm. This paper also provides evidence that owners with little or no control of a firm, take action to prevent agency costs. This action is in the form of disbursements to shareholders, rather than using debt as a means of reducing agency costs.
Keywords: 650